Avaliação do perfil inflamatório, estresse oxidativo e dos estados de humor e de ansiedade em jogadoras de futebol de campo com e sem Síndrome Pré-Menstrual (SPM) - Paiva, Roberta Foster Leonidas de [UNIFESP] (2015)
To assess the inflammatory status, oxidative stress and states of mood and anxiety disorders in the field of soccer players with and without Premenstrual Syndrome (PMS) in two phases of the menstrual cycle: follicular and luteal and at two different times: before and after a collective football (acute exercise). METHODS: We evaluated 52 competitive level of players aged between 16 and 30 years. For the determination of SPM and monitoring phases of the menstrual cycle was used questionnaire Daily Symptoms Report (DSR) validated in Portuguese for three consecutive months. For the determination of Mood States and the Anxiety BRUMS and BAI questionnaires in the four periods studied were used. Also collected urine to the four times to assess the inflammatory status and oxidative stress. RESULTS: Analysis of DSR revealed prevalence of PMS in 59.6% of athletes and prevalence of symptoms such as anxiety and water retention. The BRUMS revealed that the group with PMS had higher changes of moods in the two phases of the menstrual cycle, with greater evidence after acute exercise while the group without the SPM showed minor variation of mood and only in the luteal phase of the cycle more also evidence after acute exercise. The BAI has shown an increased state of anxiety only in the group with SPM in the two phases of the cycle, more evident prior to acute exercise. Evaluation of cytokines showed that the group with the SPM has a flash frame associated with PMS and not the exercise acute present in both phases of the menstrual cycle. The athletes with PMS also showed a likely mechanism for maintaining the concentration of oxidative and antioxidative markers in the two phases of the menstrual cycle, not altered by exercise, while no SPM group showed balance between radical production and consumption in the follicular phase and increase oxidant in the luteal phase after the collective, demonstrating the influence of exercise on oxidative mechanism / antioxidative